Wireless power transfer system - Chua, Bee Em (2014)
This project has demonstrated that 10 kW of power can be transferred between a pair of coils, spaced 70 mm apart by air. These coils are individually wrapped around an H-shaped ferrite core, compensated by the primary-series, secondary-parallel topology to achieve resonance, thereby improving the efficiency of the transformer. The design can be implemented on wireless battery charging systems for electric vehicles where the primary coils would be embedded in the ground while the secondary coils would be housed within the undercarriage of the vehicle.